The aftermath of CEO succession via hierarchical jumps on firm performance and agency cost: Evidence from Chinese firms. Issue 21 (15th December 2019) - Shah, Syed Ghulam Meran; Tang, Mingfeng; Sarfraz, Muddassar; Fareed, Zeeshan
ABSTRACT: This paper analyzes the effect of CEO succession via overall hierarchical jumps on Chinese firm performance and agency cost. It categorizes hierarchical jumps into low, medium and high level. The study reveals through panel regression analysis that the CEOs appointed via medium hierarchical jumps substantially enhance firm performance. Conversely, the successors appointed through low and high hierarchical jumps have relatively no effect on firm profitability. Conclusively, this research evaluates that the aged CEOs should be preferred among the CEOs successors via high hierarchical jumps, which have mitigated the agency problem decisively.